The descriptive epidemiology of male sex workers in Pakistan: a biological and behavioural examination. Issue 1 (17th November 2010) - Shaw, Souradet Y; Emmanuel, Faran; Adrien, Alix; Holte-Mckenzie, Merydth; Archibald, Chris P; Sandstrom, Paul; Blanchard, James F
Abstract : Objectives: There is a dearth of published information on the characteristics of sex workers in Pakistan. This study sought to characterise and compare hijra and non-hijra sex workers from eight large cities in Pakistan. Design: χ 2 and Kruskal–Wallis tests, and multivariable logistic regression were used where appropriate. Methods: Study respondents were described on demographic, sex-work, and risk behaviour variables using a cross-sectional integrated biological and behavioural quantitative survey. Results: A total of 3350 respondents were surveyed, of which 2694 were included in the study. The average age of respondents was 24.1 years (SD 6.3), and the average duration of sex work was 7.5 years (SD 5.9). Respondents averaged 30.9 (SD 2.7) paid receptive anal sex acts in the month prior to their interview, while 21.5% reported using a condom during their last occurrence of paid anal sex. Of those surveyed, HIV prevalence was 5.4 per 1000; notably, no HIV-positive respondents reported any injection drug use. Finally, intercity heterogeneity was observed on demographic, sex work and risk behaviour characteristics, with almost all characteristics differing at the p<0.01 level. Conclusions: Low levels of education, high volume of sex acts and suboptimal condom use makes for a potentially volatile situation. Information provided by this study can play an important role in designing effective prevention programmes, particularly in capturing heterogeneity in sex work between cities, and as evidence is accumulating that a shift in epidemic phase, as well as affected populations is occurring in Pakistan.